The Influence of Transaction Process With Doctors on Patient Satisfaction, Self-Rating Anxiety and Self-Efficacy Among International Students in China - Julien, Janelle; Wang, Xuemei; Meng, Han; Qian, Zhou; Wang, Dan; Zhang, Xinping (Frontiers in Public Health, 2021)
Objectives. To investigate the communication mechanism between international students and Chinese physicians by evaluating the influence of the transaction process on patient satisfaction, self-rating anxiety and self-efficacy. Methods. A cross-sectional survey was conducted among international students living in Central, Northern and Eastern China; enrolled at Chinese universities and experienced outpatient and inpatient healthcare services. Guided by the King’s transaction process, we used regression analysis to calculate the correlation and influence of the transaction process on the research outcomes. Results. Four hundred and four (404) participants were investigated for this study. The results of correlation analysis showed that there was a significant positive correlation among patient satisfaction, self-efficacy, transaction process, IR, IP, MGS, and EM (p<0.05). Regression analysis showed that the higher the scores of IR (β=0.176, p=0.003) and MGS (β=0.249, p=0.002), the higher the satisfaction; the higher the score of IR and IP, the higher the Self-efficacy score (std β=0.148,0.225; p=0.016,0.001 and; higher the MGS score, the lower the self-rating anxiety (β=-0.220, p=0.022). Conclusion. The influence of transaction process on patient satisfaction, self-rating anxiety and self-efficacy between Chinese physicians and international students (Patients) was established. Findings support the urgent implementation of tools at healthcare facilities to improve the communication between Chinese doctors and international students, therefore improving patient satisfaction and self-efficacy, and reducing anxiety.